Chemical health threats : assessing and alerting - Duarte-Davidson, Raquel; Gaulton, Tom; Wyke, Stacey; Collins, Samuel (Royal Society of Chemistry, 2019)
This book examines the European guidelines for the risk assessment and management of serious international public health threats.
Keywords: Hazardous substances -- Safety measures -- International cooperation.; Hazardous substances -- Health aspects -- Europe.; Hazardous substances -- Risk assessment -- Europe.; Hazardous substances -- Safety regulations -- Europe.; Hazardous substances -- Government policy -- Europe.; elektronické knihy; electronic books